De novo venture strategy: arch incumbency at inaugural entry - Fan, Terence Ping Ching (Strategic Management Journal, 2009)
Abstract By definition, de novo industry ventures do not share many market‐contact points with incumbents—itself an important source of competitive ‘stability’ through mutual forbearance. As such, these ventures are often subject to aggressive retaliation at the outset, which could threaten their very survival. In this study, the notion of an arch incumbent is developed, hypothesizing that, in general, a large market overlap with an incumbent lowers the survival odds of a de novo entrant. However, a large market overlap with the arch incumbent combined with an aggressive inaugural market entry or a different market positioning reduces the probability of retaliation by the arch incumbent (and subsequently other incumbents as well), and hence increases the probability of survival for a de novo entrant. The empirical experience of de novo ventures in the intra‐European passenger airline industry supports these hypotheses. Copyright © 2009 John Wiley & Sons, Ltd.